Theory of Lift : Introductory Computational Aerodynamics with MATLAB and Octave. - McBain, G. D. (Aerospace Series., 2012)
Starting from a basic knowledge of mathematics and mechanics gained in standard foundation classes, Theory of Lift: Introductory Computational Aerodynamics in MATLAB/Octave takes the reader conceptually through from the fundamental mechanics of lift€ to the stage of actually being able to make practical calculations and predictions of the coefficient of lift for realistic wing profile and planform geometries. The classical framework and methods of aerodynamics are covered in detail and the reader is shown how they may be used to develop simple yet powerful MATLAB or Octave programs that ac.